The Hit - Baldacci, David (London Macmillan, 2013)
Skilled assassin Will Robie is asked by the U.S. government to track down fellow assassin Jessica Reel, who has gone rogue, but during his pursuit of Reel, Robie realizes that her betrayal may be concealing a larger threat that could impact the whole world
Keywords: Assassins -- United States -- Betrayal